A distant perspective on how the “past” affects the “present”: the impact of early environmental unpredictability on impulsive consumption - Shijin Sun; Zhengyang Hou; Jiahui Guo; Qian Tian (Frontiers in Psychology)
IntroductionWith the growing convenience of shopping and the rise of consumerism, impulsive buying has become increasingly prevalent, sometimes leading to harmful consequences. Unlike traditional research focusing on proximal product-related factors, this study investigates the distal influence of early environmental unpredictability on impulsive buying behavior, grounded in life history theory. Additionally, the moderating role of resource scarcity is examined from a broader societal perspective.MethodsA 2×2 between-subjects factorial experimental design was employed, involving 161 participants. The independent variables were early environmental unpredictability (low vs. high) and perceived resource scarcity (scarcity vs. normal). Participants were randomly assigned to one of the four experimental conditions to explore the relationship between early environmental factors and impulsive consumption tendencies.ResultsThe findings revealed that: (1) early environmental unpredictability significantly and positively predicts impulsive buying behavior; and (2) this predictive effect is amplified under conditions of perceived resource scarcity.DiscussionThese results highlight the lasting impact of early life environments on consumer behavior and suggest that resource scarcity can exacerbate impulsive consumption. The study offers practical insights for reducing impulsive buying in modern society and contributes to interdisciplinary understanding in psychology and behavioral economics.